Analisis self-efficacy pada peserta didik di sekolah dasar se-kota surakarta - Adlian Dema Cesaria; Supianto Supianto (Didaktika Dwija Indria, 2025)
Abstract. This study aims to describe the self-efficacy of students in elementary schools in city of surakarta. The research method used is descriptive quantitative with a sample of 178 students from grades III and IV at SD Negeri Danukusuman, SD Negeri Manahan, and SD Negeri Munggung, selected using purposive sampling techniques. Data collection used a non-test method in the form of self-assessment. The instruments used have three dimensions, namely the level dimension, generality dimension, and strength dimension. The results show that the self-efficacy of students in the very good category consists of 15 students with a percentage of 8.45%, the good category consists of 89 students with a percentage of 50%, the sufficient category consists of 56 students with a percentage of 31.45%, and the inadequate category consists of 18 students with a percentage of 10.1%. All dimensions, namely the level dimension, generality dimension, and strength dimension, are categorized as good.